A molecular dynamics study of N–A–S–H gel with various Si/Al ratios. Issue 10 (15th June 2022) - Chen, Yun; Dolado, Jorge S.; Li, Zhenming; Yin, Suhong; Yu, Qijun; Kostiuchenko, Albina; Ye, Guang
Abstract: In this paper, the atomic structures of sodium aluminosilicate hydrate (N–A–S–H) gels with different Si/Al ratios are studied by molecular dynamics simulation. An N–A–S–H gel model was obtained from the polymerization of Si(OH)4 and Al(OH)3 monomers with the use of a reactive force field (ReaxFF). The simulated atomic structural features, such as the bond length, bond angle, and simulated X‐ray diffraction pattern of the gel structure are in good accordance with the experimental results in the literature. Si–O–Al is found to be preferred over Si–O–Si in the N–A–S–H gel structure according to the amount of T–O–T bond angles and distribution of Si 4 (mAl). Pentacoordinate Al is identified in all simulated N–A–S–H models. It provides strong support to current knowledge that pentacoordinate Al in geopolymer does not only come from raw material. Furthermore, the structural analysis results also show that N–A–S–H gel with lower Si/Al ratios has a more cross‐linked and compacted structure.